Kajian Trend Forecasting Ready to Wear Indonesia Trend Forecasting (ITF) 2019/2020 sebagai Pendukung Kebijakan Badan Ekonomi Kreatif (BEKRAF) - Nafisa Aninda; Setyawan setyawan (Universitas Nahdlatul Ulama Pasuruan, 2021)
Humans are creatures that continue to change and develop every time. This is influenced by the progress experienced by humans, especially in the field of technology. Trend Forecasting Indonesia promoted by the association Indonesia Trend Forecasting (ITF) opens reasoning for new perspectives, changes perceptions and becomes a reference for creative economy actors in Indonesia. The purpose of this research is to open new insights on trend forecasting and its scope in design thinking. This study uses qualitative research methods with an anthropological approach to cultural policy and theory from Shore & Wright. Data were obtained by passive observation, in-depth interviews, and literature study. This study focuses on the background of trend forecasting in Indonesia and Bekraf policies that affect creative economy actors. The results of this study are the background of trend forecasting in Indonesia starting from the problem of Indonesian products that do not compete in the market, creative work policies that are supported and in line with forecasting trends in Indonesia, as well as the influence on policies and the expansion of trend forecasting in Indonesia.